PEMBERDAYAAN MASYARAKAT BERBASIS KOPERASI PADA TAMBANG MINYAK TRADISIONAL DESA BANGOAN KECAMATAN JIKEN KABUPATEN BLORA - Setiawan, Tomi Uki; Taufiq, Ahmad; Astrika, Lusia (Journal of Politic and Government Studies, 2017)
Abstract: The Empowering Community Based Cooperative On Traditional Oil Mines, Bangoan Village Jiken Subdistrict Blora RegencyIn Indonesia, there are 4.000 old oil wells that are not expluitd by pertamina because it is not economical. Some of old wells are exploited in traditional way, one of them in bangoan village, jiken subdistrict, blora regency. Oil wells left by pertamina because it is not economical, the production is low but the expense of production is too high. So the surrounding communities who live around the oil mining, they explore the mining traditionally. Because the mining is considered illegal, finally there is a that manages the oil wells, one of them is kud wargo tani makmur. With the management of kud wargo tani makmur is expected to improve the welfare of communities around the location of traditional oil mines, by including the participation of communities around them.This research was conducted to know the role of traditional oil mines to the welfare of communities by using qualitative method. Technique of collecting data is done by interview, documentation and literature study. The validity and reliability of data were tested using source triangulation techniques.The result of research show that the trsditional oil mining has provided new jobs, incseased incomes, reduced unemployment and better welfare of village communities with integrated empowerment covering capital, infrastructure development, and human resource quality improvement.Community empowerment in Bangoan village should be further improved, both from economic aspect, knowledge, training and guidance to miners. And the need for better environmental sustainability so that the economy and the welfare of the community are more secure.Keyword : the empowering, the traditional oil mines, the roles